Climate change and the distribution of frozen soil in 1980–2010 in northern northeast China. (22nd February 2018) - Zhang, Zhongqiong; Wu, Qingbai; Xun, Xueyi; Wang, Boxin; Wang, Xunan
Abstract: Frozen soil is an important environmental factor in cold regions. Permafrost change, driven by a warming climate, will increase the risk of permafrost thawing, i.e., carbon release accelerating, suprapermafrost water lowering, desertification strengthening, and infrastructure destructing. Based on the energy balance between the atmosphere and the soil, mean annual air temperature (MAAT), annual precipitation (AP), and mean annual wind speed (Vs) were selected for the analysis of the patterns of permafrost environment and its dynamics from 1980 to 2010 in northern northeast China. According to data from meteorological stations, MAAT and Vs increased with the decrease of latitude in the study area, whereas AP increased with the increase of longitude. During 1980 to 2010, the average of MAAT, Vs, AP, freezing index (DDF), and thawing index (DDT) in the study area was −0.73 °C, 473.5 mm, 2.44 m s −1,  −2696.7 °C·d −1, and 2458.0 °C·d −1, respectively. Compared with the condition in 1980, the area with MAAT less than 0 °C decreased by 15.8%, 500 mm isotherms of AP moved to the east, the area with Vs of less than 2.2 m/s was expanding, and the area with DDF larger than DDT decreased by 16.9%. The 0 °C isotherm moved to the north and high-altitude direction. The area of permafrost was decreased by 13.67% from 1980 to 2010. However, the area with sparcely island permafrost expanded because of the increase in precipitation, especially in the southeast area. MAAT, Vs, and AP influenced the change and distribution of permafrost, among which MAAT was the dominant factor. The influence of Vs and AP gradually decreased from south to north. Changes in the permafrost environment and distribution would directly affect the vegetation succession and ecological environment. This work will provide basic data for regional research on frozen soil and environment in northern Northeast China.